Hambatan Sosial Budaya dalam Pelayanan Kesehatan pada Komunitas Tradisional: Studi Literatur - Akhlish Dzikrullah Ahmad; Margaretha Hanita; Renny Nurhasana (ETNOREFLIKA: Jurnal Sosial dan Budaya, 2025)
Traditional communities in various regions of Indonesia continue to face multiple barriers in accessing modern healthcare services. These barriers are not only geographical and structural but also socio-cultural in nature. This article aims to identify and analyze socio-cultural barriers affecting healthcare access and utilization among traditional communities through a systematic literature review. The study employed a literature review approach by searching for scholarly articles in PubMed, Scopus, Google Scholar, and ISJD databases published between 2015 and 2025. In total, 41 articles were retrieved and analyzed from these databases. Inclusion criteria encompassed studies addressing socio-cultural barriers and the integration of traditional and modern medicine within healthcare services for traditional communities in Indonesia. Five key socio-cultural barriers were identified: (1) reliance on traditional healing systems; (2) communication gaps between healthcare providers and communities; (3) social values and norms that restrict access; (4) incongruence between healthcare services and cultural needs; and (5) stigma toward disease and modern medicine. These barriers significantly influence service quality and accessibility. Culturally responsive strategies are therefore required, including the integration of traditional and modern medicine, enhancement of healthcare workers’ cultural competence, empowerment of local cadres, and the adaptation of services to align with community cultural values, in order to improve healthcare access and quality among Indigenous populations.